Evaluation of severe obstructive sleep apnea/hypopnea syndrome after maxillomandibular advancement surgery - Fernanda Louise Martinho (Einstein (São Paulo), 2007)
Objective: To evaluate the effectiveness of the maxilomandibularadvancement surgery in patients suffering from obstructive sleepapnea/hypopnea syndrome by analysing it objectively and subjectively.Methods: Ten patients suffering from apnea/hypopnea syndrome indexabove 30 events per sleep hour, diagnosed by polysomnography wereexamined. The patients underwent physical, polysomnographic andcephalometric tests and were subjectively evaluated according to theEpworth Sleepness Scale. The data obtained was compared to theresults of the same group 6 months after the surgery. Results: Afterthe maxilomandibular advancement surgery, as related to an objectiveevaluation by polysomnography, the results were the following: 20% ofthe patents had a normal apnea/hypopnea index, 30% of the patientshad a moderate apnea/hypopnea index and 40% of the patients kepta severe apnea/hypopnea index, 60% of the patients had a 50%decrease in the apnea/hypopnea index and only 10% of the patientshad an increase in the apnea/hypopnea index. The average of thelowest oxyhemoglobin saturation in the preoperative was 63.4%, anda significant improvement was obtained after the maxilomandibularadvancement procedure when an average of 80.8%, and 70% of thepatients showed a lowest oxyhemoglobin saturation above 83%. Asfor the subjective evaluation using the Epworth Sleepness Scale,there was an improvement in 100% of the patients. Conclusions: Theobjective evaluation of the maxilomandibular advancement surgeryshowed that it was effective in 60% of the patients suffering fromsevere apnea/hypopnea index, while the subjective evaluation showedthat it was effective in 100% of the patients.